The Study of Mechanisms of Protective Effect of Rg1 against Arthritis by Inhibiting Osteoclast Differentiation and Maturation in CIA Mice - Gu, Yanqing; Fan, Weimin; Yin, Guoyong (Mediators of Inflammation, 2014)
Ginsenoside Rg1 is a natural product extracted from Panax ginseng C.A. Although Rg1 protects tissue structure and functions by inhibiting local inflammatory reaction, the mechanism remains poorly understood. In vitro, Rg1 dose-dependently inhibited TRAP activity in receptor activator of nuclear factor-κB ligand- (RANKL-) induced osteoclasts and decreased the number of osteoclasts and osteoclast resorption area. Rg1 also significantly inhibited the RANK signaling pathway, including suppressing the expression of Trap, cathepsin K, matrix metalloproteinase 9 (MMP9), and calcitonin receptor (CTR). In vivo, Rg1 dramatically decreased arthritis scores in CIA mice and effectively controlled symptoms of inflammatory arthritis. Pathologic analysis demonstrated that Rg1 significantly attenuated pathological changes in CIA mice. Pronounced reduction in synovial hyperplasia and inflammatory cell invasion were observed in CIA mice after Rg1 therapy. Alcian blue staining results illustrated that mice treated with Rg1 had significantly reduced destruction in the articular cartilage. TRAP and cathepsin K staining results demonstrated a significant reduction of numbers of OCs in the articular cartilage in proximal interphalangeal joints and ankle joints in Rg1-treated mice. In summary, this study revealed that Rg1 reduced the inflammatory destruction of periarticular bone by inhibiting differentiation and maturation of osteoclasts in CIA mice.